Photoinduced self-assembly of nanocrystals inside Al2O3-Lu2O3 glass - Okuno, Tatsuya; Shimotsuma, Yasuhiko; Shimizu, Masahiro; Miura, Kiyotaka (Advanced Optical Technologies, 2023)
The femtosecond laser direct writing technique can allow spatially selective crystallization with suppression of thermal conduction effects. In the case of Al2O3-R2O3 (R = Y, Dy) glass, the polarization-dependent periodic nanostructure with crystallization is self-assembled, however, the formation mechanism of self-assembled nanocrystals in glass remains to be clarified. We focused on Al2O3-Lu2O3 glass prepared by a containerless laser melting method and demonstrated the formation of a nanograting with crystallization by femtosecond laser irradiation. Polarized luminescence measurements of the crystallized region by the pulse bursts with a controllable number of pulses reveal that luminescence anisotropy increased at more than 50 pulses in a burst, suggesting the formation of the nanograting. We have also followed the time variation of birefringence by polarized light imaging to evaluate the time scale for the formation of nanogratings with crystallization.